Evaluation of seismic response of coupled wall structure with self-centering and viscous damping composite coupling beams. (November 2022) - Li, Yong; Jin, Tianjiao; Meng, Shaoping; Yu, Haifeng; Zhao, Yuanyuan
Abstract: In order to reduce the residual displacement and floor acceleration of coupled wall structures, a novel self-centering and viscous damping composite coupling beam is proposed. The proposed coupling beam consists of the elastic beam segments and the fuse part, which incorporates self-centering friction dampers and viscous dampers. The self-centering friction damper can provide strength and stiffness for the proposed coupling beam and reduce the residual displacement of the coupled wall structure. The viscous damper can add supplemental damping to the system, and this can control the peak lateral displacement demands and floor accelerations of the structure. Moreover, the proposed coupling beam can eliminate the beam elongation effect of the self-centering coupling beam with a rocking behavior. Design methodology and nonlinear numerical model of the proposed coupling beam are developed. The seismic behaviors of the coupled wall structure with the self-centering and viscous damping composite coupling beams (CW-SCVCCB) are assessed and compared with the structure with reinforced concrete coupling beams (CW-RCCB), the structure with steel coupling beams (CW-SCB) and the structure with self-centering coupling beams (CW-SCCB). Analysis results showed that the supplemental viscous damping can effectively reduce the peak interstory drift ratio and floor accelerations of the structure. The residual displacement of the novel coupled wall system is larger than that of the CW-SCCB, however, it is significantly reduced compared with the CW-SCB and the CW-RCCB.